Oleate induces apoptosis in 3T3-L1 adipocytes - Rohana, Abu; Fadzilah Adibah, A. M.; Muhammad Roji, M. S. (World Academy of Science, Engineering and Technology, 2011)
Oleic acid (C18:1) play an important role in proliferation of fat cells. In this study, the effect of oleate on cells viability in 3T3-L1 cells (fat cells) was investigated. The 3T3-L1 cells were treated with various concentrations of oleate in the presence of 23 mM glucose. Oleate was added to adipogenic media (day 0) to investigate the influence of oleate on proliferation of postconfluent preadipocytes after 24 h induction. 0.1 mM oleate promoted cell division by increasing 33.9% number of cells from basal control in postconfluent preadipocytes. However, there were no significantly different in cells viability with control cells when oleate concentrations were increased up to 0.5 mM. When added to differentiated adipocytes (day 12) for 48 h, the number of cells decreased as oleate concentrations increased. 92.7% of cells lost demonstrated apoptosis and necrosis after 48 h with 0.5 mM oleate. The fluorochrome staining was examined under fluorescence microscopy using acridine orange and ethidium bromide double staining. Furthermore, the presence of high lactate (60.6% increased from basal control) released into plasma has shown the direct cytotoxicity of 0.5 mM oleate on adipocytes. Keywords—adipocytes, apoptosis, oleate, postconfluent preadipocytes.